The path towards the European integration. The case of Poland. Economic restructuring versus integration processes - SZUL, Roman; MYNC, Agnieszka (European Spatial Research and Policy, 1997)
The paper describes evolution of the political and economic situation which led to and accompanied the creation of market economy and parliamentary democracy as well as changes in the institutional system in Poland. The paper concentrates on economic issues, in particułar on several aspects of the economic performance and policy after 1989, such as general trends, privatisation, foreign investment, unemployment, social and environmental issues, etc. in two stages of transformation: (1) the period of output decline and creation of basis for market economy; (2) the period of recovery. After this presentation, the paper analyses weaknesses and strengths of Poland's economy in the perspective of its integration in the EU.